Intercultural communication between colombian and american teachers in colombian institutions (2009)
This article, which is based on observations from working in multicultural environments for twentyfive years and a review of sources on intercultural communication, addresses the intrinsic difficulties that arise from communication among people of different cultures. The connection between language and culture is so close that communication among internationals creates challenges of intercultural communication even when communicating in the same language. In Colombia, especially in institutions that teach English, there are bicultural or multicultural groups of teachers that work together. Some misunderstandings arise because of an inadequate understanding of colleagues’ values systems. This article includes three common work situations, the possible problems arising from inappropriate communication and some suggestions for overcoming intercultural communication difficulties. Key words: Intercultural communication, globalization, challenging intercultural relationships, foreign language teachers Este artículo, basado en mis observaciones de 25 años de trabajo en ambientes multiculturales y en una revisión de fuentes sobre la comunicación intercultural, trata sobre las dificultades intrínsecas que surgen de la comunicación entre gente de distintas culturas. El lenguaje está tan relacionado con la cultura que la comunicación entre internacionales crea desafíos de comunicación intercultural, aún cuando se comunican en el mismo idioma. En Colombia, especialmente en instituciones donde se enseña inglés, se encuentran grupos de docentes de distintos países que trabajan juntos y cuyos valores son diferentes. Surgen malos entendidos a raíz de una falta de comprensión del sistema de valores del otro. Este artículo incluye tres situaciones comunes en el lugar de trabajo, algunos problemas que pueden aparecer en él debido a una comunicación inapropiada y algunas sugerencias para superar dificultades en la comunicación intercultural. Palabras clave: Comunicación intercultural, globalización, relaciones interculturales desafiantes, docentes de lenguas extranjeras